“Spirituality... we do not have such a thing”: Patrimonialization processes as minefields - Claudia Briones (Nuevo mundo - Mundos Nuevos, 2017)
Based on various situations and initiatives, which show the dynamics of the politics of recognition of indigenous patrimony, I identify several paradoxes. First, those arising from the languages enabled by the political struggle for indigenous rights. Then, the metacultural disputes which become apparent in and through that struggle. Finally, the tensions that result unavoidably from the attempt to equalize different economies of value and affection, and different regimes of historicity. On this basis, I propose a critical reading of the contemporary governmentality, by means of exploring invisibilized claims. I focus on the invisibilization of claims that put into question a given patrimonialization, or that aim at the patrimonialization of what is seen as a flaw of the hegemonic attempts of fixing accents about history, places of memory, or the environment. Once the unstable horizons of meaning linked to patrimonialization processes are identified, I explore some alternatives to walk through these “minefields”, inherited from previous wars and current skirmishes.